Toward high-capacity carbon fiber cathodes for structural batteries using electrophoretic deposition: effects of oxidative surface treatment on carbon fibers - Nur Ayu Afira Sutrisnoh (2024)
Structural batteries possess multifunctional capability to store electrochemical energy and carry mechanical load concurrently. Carbon fiber cathodes (CFC), one of the main components in structural batteries, can be fabricated by depositing cathode active materials on carbon fibers using techniques such as electrophoretic deposition (EPD). However, intrinsically inert surface of carbon fibers may result in weak adhesion. In this study, different oxidative surface treatments (acid, electrochemical, and heat) are evaluated based on their ability to activate surfaces of carbon fibers. The mechanical and electrochemical performance of resultant CFC fabricated with lithium nickel manganese cobalt oxide (NMC 111) via EPD are analyzed. The best-performing CFC are achieved using acid-oxidized carbon fibers due to their improved interfacial adhesion. Acid-oxidized AS4C 3k CFC yield a high specific capacity of 151 mAh g−1 after 100 cycles at 1 C and are stable over 100 cycles at 1 C with capacity retention close to 100% and give a stiffness of 25 GPa and ultimate tensile strength of 260 MPa. Acid-oxidized 12k CFC show higher mechanical performance with stiffness of 53 GPa and ultimate tensile strength of more than 500 MPa, which make them more favorable to be used for structural batteries.